Experimental study of mechanical properties of AA6061 and AA7075 alloy joints using friction stir welding. (2021) - Amuthan, Tamilselvan; Nagaprasad, Nagaraj; Krishnaraj, Ramaswamy; Narasimharaj, Venugopal; Stalin, B.; Vignesh, Venkataraman
Highlights: This paper explores the mechanical properties of AA6061 and AA7075 alloy joints using FSW. Al alloys usage in the field of aerospace and automotive is increased due to excellent S/W ratio. Focus the parametric effects on various mechanical properties through Taguchi method. Abstract: The primary aim behind this work is to calibrate the welding parameters effect on the mechanical properties of friction stir welded butt joints made of dissimilar aluminium alloys AA6061 and AA7075. A new solid-state joining process is FSW (Friction stir welding) and this method of joining is energy-efficient, cost-effective, environmentally friendly, and adaptable. Friction stir welding is used in aerospace for joining aluminium alloys and other metallic alloys that are difficult to weld using traditional fusion welding techniques. In this process, two metal pieces namely AA6061 and AA7075 of dimensions 100 × 50 × 6 mm, are welded by considering the effect of parameters like tool rotation speed and transverse feed. The effects of welding parameters were assessed by looking at the resulting mechanical properties of the axial welded field, such as hardness distribution and wear properties.